Organization at criticality enables processing of time‐varying signals by receptor networks - Angel Stanoev; Akhilesh P Nandan; Aneta Koseska (Molecular Systems Biology, 2020)
Abstract How cells utilize surface receptors for chemoreception is a recurrent question spanning between physics and biology over the past few decades. However, the dynamical mechanism for processing time‐varying signals is still unclear. Using dynamical systems formalism to describe criticality in non‐equilibrium systems, we propose generic principle for temporal information processing through phase space trajectories using dynamic transient memory. In contrast to short‐term memory, dynamic memory generated via “ghost” attractor enables signal integration depending on stimulus history and thereby uniquely promotes integrating and interpreting complex temporal growth factor signals. We argue that this is a generic feature of receptor networks, the first layer of the cell that senses the changing environment. Using the experimentally established epidermal growth factor sensing system, we propose how recycling could provide self‐organized maintenance of the critical receptor concentration at the plasma membrane through a simple, fluctuation‐sensing mechanism. Processing of non‐stationary signals, a feature previously attributed only to neural networks, thus uniquely emerges for receptor networks organized at criticality.